La necesidad de aplicar medidas cautelares al infractor en delitos de ejercicio privado de la acción penal - Cerezo Escobar, Lisbeth del Rocío (2019)
The present work deals with the personal and real precautionary measures and their application in the Ecuadorian criminal procedural law. The same as the purpose of ensuring the appearance of the defendant to the process and the compensation to which a victim is entitled. A study is made of the different types of Ecuadorian processes, both in private action, and public action, focusing on the issue of precautionary measures. From Article 647 to 651 of the Comprehensive Criminal Code. The procedure for the substantiation and trial of the crimes for which the action was private is established……